Nutrients in water column from Young Sound, NE Greenland - Ingrid Wiedmann; Maria Lund Paulsen; Johnna M Holding; Mie Hylstofte Sichlau Winding; Hans Roy; Mikael K Sejr; Katja Laufer-Meiser (PANGAEA, 2025)
This dataset contains measurements of nutrients in the water column of Young Sound (NH3, Si, NOx, PO4). The samples for the measurements were taken in August 2019 with a small Niskin bottle rosette (12x1.2L) or by repeated casts of a 5L Niskin bottle.
In: Wiedmann, I et al. (2025): Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986456